2001
DOI: 10.1080/14015430152728025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sound amplification on teachers' speech while teaching

Abstract: Voice problems are common among teachers. This is most likely due to the heavy vocal load of their profession. The present study investigated one possible method to decrease the vocal load. The effects of amplification on classroom speech were studied on five Icelandic teachers (three females, two males, mean age 51 years). Classroom speech was recorded with a portable DAT recorder and a head-mounted microphone, first under ordinary conditions and in the next week while using electrical sound amplification. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…With regard to the point of view of the children, most of the teachers in the study reported that children became immediately used to the novelty, and they also benefitted from listening. Also this aspect is in agreement with some previous reports indicating that poor voice quality in teachers reduces the intelligibility of speech [14,15,24,25], while amplification both reduces the need for repetition and permits better concentration [15].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With regard to the point of view of the children, most of the teachers in the study reported that children became immediately used to the novelty, and they also benefitted from listening. Also this aspect is in agreement with some previous reports indicating that poor voice quality in teachers reduces the intelligibility of speech [14,15,24,25], while amplification both reduces the need for repetition and permits better concentration [15].…”
Section: Discussionsupporting
confidence: 81%
“…Despite an increase in the selection and popularity of voice amplification in the classroom, only sporadic studies have objectively evaluated the effects of these instruments on reducing the speaker's vocal demand. In the first years of this decade, a few studies demonstrated that portable systems permit up to 6.0 dB SPL reduction of the voice intensity during a simulated classroom lecture [12][13][14]. Furthermore, among a group of 33 teachers, 97% reported easier voice production and 82% found improved vocal endurance [15].…”
Section: Methodsmentioning
confidence: 99%
“…The voice pitch is a sensitive indicator for voice load [22,23]. A correlation of voice pitch (mean and standard deviation) of vowels with voice loading in different rooms could be observed in our study: in acoustically better rooms the mean voice pitch before/after teaching decreased stronger than in unfavourable rooms.…”
Section: Kob Et Al: Influence Of Room Acoustics On the Teacher's supporting
confidence: 50%
“…It is also observed that the national experiences do not present action involving vocal amplification, pointed out in the international literature as an option to improve and facilitate the vocal production of the teacher (11,12,29) . In the perspective of health promotion, it is necessary to re-examine the vocal health intervenient and determining factors and identify the directions necessary to face the challenges.…”
Section: Discussionmentioning
confidence: 97%
“…It is interesting to point out that, in spite of several publications that subsidize reflection on the relations involving work conditions, environment and organization and teachers' health (16,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) , the educative actions in vocal health structured from such assumptions still are rare. The results are alarming, now that some authors (25) claim that there is a limit to the efficiency of the speech therapy action without the transformation of the work conditions and organization.…”
Section: Discussionmentioning
confidence: 99%